Correlation of larval population of Heliothis armigera with yield parameters of pigeonpea (Cajanus cajan) - KHANDWE, K; MACHWE, V G; KHANDWE, R (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during 1992 and 1993 to find out the correlation between Heliothis larval densitiesand yield attributing paramaters of pigeonpea (Cajanus cajan (L.) Millsp.). There was a negative correlation betweenlarval intensity and number of pods, grains and their weight while positive correlation with pod damage at green anddry stage. With an increase of one larva/plant there was a decrease of 4.95 green pods, 7.05 dry pods, 18.01 grains, 3.79g pod and 2.05 g grain weight/plant, whereas pod damage increased 2.61 and 4.93% at green and dry stage respectively.